Exploring older adults' experiences using technology during a viral pandemic. (December 2021) - Barber, Justin M; Scherer, Sally; Rhodus, Elizabeth K; Kelly, Parsons R; Johnson, Julia; Hall, Megan; Snyder, Katherine; Coy, Beth; Boggess, Bailee; Lowry, Kimberly; Shaffer, Andrea; McRoberts, Tyler; et al.
Abstract: Background: Older adults are at greater risk for morbidity and mortality associated with COVID‐19. Spatial distancing and sequestering practices are recommended to limit viral exposure. Older adults adopting these practices are at increased risk of social isolation and adverse health outcomes. Remote technologies offer various platforms for satisfying socialization and healthcare needs while sequestering. Understanding how older adults are using technology has implications for wellbeing during a pandemic. Method: Researchers attempted to contact all participants enrolled in the University of Kentucky Alzheimer's Disease Research Center longitudinal study via telephone to survey technology use (n = 706). Participants were contacted directly, except for demented participants, whose primary caregivers were contacted to respond on their behalf, when possible. Participants and caregivers gave their assent verbally to complete the voluntary survey, the procedures of which were approved by the IRB. The surveys consisted of validated instruments to gauge the extent of use of and comfort with technology. Spearman correlations, chi‐square tests, and t‐tests were used to explore data. Result: Ultimately, 384 participants were reached and 332 consented to participate. Most reported reliable home internet access (91.5%) and some internet use (90.6%). Recent feelings of loneliness were not related to any technology‐related variables (all p s > 0.29) other than decreasing with greater willingness to use telehealth ( Rho = ‐0.11, p = 0.06). Those who reported a lack of comfort with technology ( n = 76) were less likely to text messaging (67% vs 78%) and social media (56% vs 69%), p s ≤ 0.06, but felt socially connected using technology at similar levels (82% vs 75%), p = 0.22. Nearly 70% of this group reported they would use technology more with training. Across all participants, willingness to use telehealth was not related to frequency of frustration with tech ( Rho = 0, p = 0.99). Conclusion: The results suggest that some older adults' use of technology is limited by familiarity. Lack of familiarity does not appear to create a barrier to using telehealth nor does frustration with technology appear to limit telehealth use. The findings have implications for supporting older adults sequestered during a pandemic but potentially more broadly.